1999
DOI: 10.2519/jospt.1999.29.8.444
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Stability With ACL Impairment

Abstract: Study Design: Repeated measures (3 separate day sessions) to determine test reliability; single-session repeated measures to compare stability between limbs. Objectives: To develop a functional test measuring dynamic stability that is capable of differentiating between the injured and uninjured lower limb in 2 populations: (1) people with anterior cruciate ligament deficiency (ACLd) and (2) people with anterior cruciate ligament reconstruction (ACLr), and to establish the reliability of this test. Background: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 18 publications
2
123
1
3
Order By: Relevance
“…Since impact forces are high, DPSI emphasizes more the landing rather than the stabilizing phase [13]. Both TTS and DPSI have shown higher outcome values for subjects with chronic ankle instability [14][15][16], or with ACL reconstruction [17,18], compared to healthy controls. However, their applicability with regard to injury risk and monitoring of rehabilitation still needs to be elucidated [6,13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Since impact forces are high, DPSI emphasizes more the landing rather than the stabilizing phase [13]. Both TTS and DPSI have shown higher outcome values for subjects with chronic ankle instability [14][15][16], or with ACL reconstruction [17,18], compared to healthy controls. However, their applicability with regard to injury risk and monitoring of rehabilitation still needs to be elucidated [6,13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Ten trials were completed on each limb. 24 Although these athletes were exposed regularly to strenuous activity, including jumping, a 1-minute rest was given between trials to avoid fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…The time-to-stabilization (TTS) measurement technique is used to assess the time that participants take to attain a stable position after a jump-landing task, giving an indication of dynamic postural stability. Colby et al, 24 who were the first to study this technique, compared the stabilization times of unilateral ACL-deficient and ACLR knees with the contralateral healthy knees in recreationally active patients. They found that TTS was a reliable means for identifying a deficit in dynamic postural stability in those with ACL injury while performing a step-down task.…”
Section: Journal Of Athletic Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Há, na literatura, uma série de trabalhos que têm investigado a simetria em tarefas unipedais, em sujeitos submetidos à reconstrução cirúrgica do LCA (Novak, Bach et al, 1996;Bach, Trdonsky et al, 1998;Colby, Hintermeister et al, 1999;Hoffman, Schrader et al, 1999;Rudroff, T., 2003;Gustavsson, Neeter et al, 2006). Em tarefas como o apoio unipedal, como o salto vertical unipedal, esses sujeitos tendem a apresentar déficits no membro operado em relação ao membro sadio.…”
Section: Introductionunclassified